Violence, Development and Migration Waves: Evidence from Central American Child Migrant Apprehensions - Michael A. Clemens (Institute of Labor Economics (IZA), 2017)
A recent surge in child migration to the U.S. from Honduras, El Salvador, and Guatemala has occurred in the context of high rates of regional violence. But little quantitative evidence exists on the causal relationship between violence and international emigration in this or any other region. This paper studies the relationship between violence in the Northern Triangle and child migration to the United States using novel, individual-level, anonymized data on all 178,825 U.S. apprehensions of unaccompanied child migrants from these countries between 2011 and 2016. It finds that one additional homicide per year in the region, sustained over the whole period – that is, a cumulative total of six additional homicides – caused a cumulative total of 3.7 additional unaccompanied child apprehensions in the United States. The explanatory power of short-term increases in violence is roughly equal to the explanatory power of long-term economic characteristics like average income and poverty. Due to diffusion of migration experience and assistance through social networks, violence can cause waves of migration that snowball over time, continuing to rise even when violence levels do not.
Keywords: D74; F22; K42; O15; R23; 330; violence; migration; forced; refugee; UAC; unaccompanied children; Northern Triangle; Central America; Honduras; Guatemala; El Salvador; minors; survival migration; youths; Cartagena Declaration; Global Compact; war; drug trade; smugglers; traffickers; trafficking; cocaine; cartel; gang; mara; homicide; murder; mobility; asylum; asylee; war; deaths